2009
DOI: 10.1080/10715760903171100
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol protects against irradiation-induced hepatic and ileal damage via its anti-oxidative activity

Abstract: The present study was undertaken to determine whether resveratrol (RVT) could ameliorate ionizing radiation-induced oxidative injury. After a 10-days pre-treatment with RVT (10 mg/kg/day p.o.), rats were exposed to whole-body IR (800 cGy) and the RVT treatment was continued for 10 more days after the irradiation. Irradiation caused a significant decrease in glutathione level, while malondialdehyde levels, myeloperoxidase activity and collagen content were increased in the liver and ileum tissues. Similarly, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…It is worth noting that there is evidence that RV can act as an ROS scavenger in normal cells to protect against ionizing radiation-induced oxidative stress and tissue injury [52], suggesting that RV may have differential effects on ROS production in normal versus cancer cells. Given that aberrant redox systems are frequently observed in many tumor cells [48], [53], [54], it is possible that RV may selectively suppress the growth of tumor cells with little or no toxicity to normal cells due to their differential redox status.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that there is evidence that RV can act as an ROS scavenger in normal cells to protect against ionizing radiation-induced oxidative stress and tissue injury [52], suggesting that RV may have differential effects on ROS production in normal versus cancer cells. Given that aberrant redox systems are frequently observed in many tumor cells [48], [53], [54], it is possible that RV may selectively suppress the growth of tumor cells with little or no toxicity to normal cells due to their differential redox status.…”
Section: Discussionmentioning
confidence: 99%
“…Though rhodanese is not induced by DADS, it has been reported that it is induced by resveratrol [24] and that its activity is promoted by α-lipoic acid (LA) [25]. Resveratrol mitigates radiation-induced damage [26] and has been demonstrated to accumulate in the liver and protect hepatocytes from oxidative stress [27]. It has been observed that LA has radioprotective abilities [28], and the effects of LA on anti-stress responses are considered to be due to its anti-oxidative potential [29].…”
Section: Rhodanese Inducers and Radioprotective Functionsmentioning
confidence: 99%
“…For biological decontamination of the packed food supplies the impermeable containers are boiled for 15 min/washed with soap and water followed by immersing in disinfectant solutions such as chlorine, bleaching solution, 5 per cent sodium carbonate, HTH (calcium hypochlorite) solution, super tropical bleach (STB) solution, 2 per cent per acetic acid. and aeration of the containers 41 . For nuclear decontamination the supplies must be washed with soap water followed by rinsing or brushing and wiping the contamination from surface.…”
Section: Effect Of Cbrn Agents On the Quality Of Food And The Decontamentioning
confidence: 99%